1973
DOI: 10.1007/bf00829855
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the internal mass transfer under isothermal conditions

Abstract: A study has been made concerning the effect of an electric and a magnetic field as well'as the effect of exchange ions on the internal mass transfer in the case of moisture sorption in grade KSM-5 silica gel in a constant-temperature and constant-pressure atmosphere of water vapor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…For an applied voltage difference of 6 kV, a significant enhancement in the adsorption rate behavior is noted. It was suspected that these industrial gel samples might have contained some ionic impurities which are known to affect the adsorption characteristics (Panchenko, 1973). Samples…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For an applied voltage difference of 6 kV, a significant enhancement in the adsorption rate behavior is noted. It was suspected that these industrial gel samples might have contained some ionic impurities which are known to affect the adsorption characteristics (Panchenko, 1973). Samples…”
Section: Resultsmentioning
confidence: 99%
“…As observed by Panasyuk et al (1978) in the case of CC14, the adsorption behavior of nonpolar adsorbates seems to be unaffected by applied electric fields. Panchenko et al (1973Panchenko et al ( , 1972 have suggested that the enhancement of adsorption kinetics in porous media is only possible in nonuniform applied fields and that uniform applied fields produce no effect. Panchenko et al (1973) used a uniform field of about 2 kV/cm and saw no effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations